STRATEGI PENCEGAHAN DAN PEMBERANTASAN AKSI BALAPAN LIAR DI KALANGAN REMAJA - NI PUTU NONI SUHARYANTI; Ni Komang Sutrisni (Jurnal Hukum Saraswati (JHS), 2020)
Teenagers are a transition from children to adulthood. Adolescence often makes someone look unstable, so it is susceptible to negative behavior if there is a lack of control or supervision. One form of delinquency that is often done by adolescents is wild racing, where the impact is not only on oneself but also the surrounding environment. In preventing and combating illegal racing action among adolescents requires a strategy that is not only the main task of the Police, but all groups ranging from parents, schools, and the wider community. Various types of approaches also need to be taken, both internal and external approaches based on local wisdom, so that the Police can create synergy with families, schools, youth organizations, nongovernmental organizations, as well as traditional security forces in the local village. Keywords : , , ,